"Eavesdropping on Happiness" Revisited: A Pooled, Multisample Replication of the Association Between Life Satisfaction and Observed Daily Conversation Quantity and Quality. (September 2018) - Milek, Anne; Butler, Emily A.; Tackman, Allison M.; Kaplan, Deanna M.; Raison, Charles L.; Sbarra, David A.; Vazire, Simine; Mehl, Matthias R.
In the present study, we aimed to replicate and extend findings by Mehl, Vazire, Holleran, and Clark (2010) that individuals with higher well-being tend to spend less time alone and more time interacting with others (e.g., greater conversation quantity) and engage in less small talk and more substantive conversations (e.g., greater conversation quality). To test the robustness of these effects in a larger and more diverse sample, we used Bayesian integrative data analysis to pool data on subjective life satisfaction and observed daily conversations from three heterogeneous adult samples, in addition to the original sample ( N = 486). We found moderate associations between life satisfaction and amount of alone time, conversation time, and substantive conversations, but no reliable association with small talk. Personality did not substantially moderate these associations. The failure to replicate the original small-talk effect is theoretically and practically important, as it has garnered considerable scientific and lay interest.